Anti-inflammatory effect of galectin-1 in a murine model of atopic dermatitis - Corrêa, Mab Pereira [UNESP]; Andrade, Frans Eberth Costa; Gimenes, Alexandre Dantas; Gil, Cristiane Damas [UNESP] (Springer Nature, 2017)
Abstract: Atopic dermatitis (AD) is caused by both dysregulated immune responses and an impaired skin barrier. Although beta-galactoside-binding protein galectin-1 (Gal-1) has immunomodulatory effects in several inflammatory disorders, therapeutic strategies based on its anti-inflammatory properties have not been explored in AD. Thus, we evaluate pharmacological treatment with Gal-1 in the progression of an ovalbumin (OVA)-induced AD-like skin lesions. The skin of OVA-immunized male BALB/c mice was challenged with drops containing OVA on days 11, 14–18 and 21–24. Additionally, in the last week, a subset of animals was treated intraperitoneally with recombinant Gal-1 (rGal-1) or dexamethasone (Dex). Treatment with rGal-1 decreased the clinical signs of dermatitis in BALB/c mice and diminished local eotaxin and IFN-γ levels. The treatment also suppressed the infiltration of eosinophils and mast cells, which was verified by reduced expression of mouse mast cell protease 6 (mMCP6) and eosinophil peroxidase (EPX). These localized effects are associated with extracellular signal-regulated kinase (ERK) activation and downregulation of endogenous Gal-1. The inhibition of disease progression induced by rGal-1 was also correlated with reduced plasma IL-17 levels. Our results demonstrate that rGal-1 is an effective treatment for allergic skin inflammation in AD and may impact the development of novel strategies for skin inflammatory diseases. Key messages: Pharmacological treatment with rGal-1 reduces clinical signs of atopic dermatitis.Systemic treatment with rGal-1 inhibits eosinophil and mast cell influx in the skin of AD animals.rGal-1 reduced local eotaxin levels and systemic IL-17 levels.The inhibition of disease progression induced by rGal-1 was correlated with upregulation of phosphorylated ERK.
Keywords: Eosinophil; ERK; Galectin-1; Mast cell; Ovalbumin; Skin inflammation